Assessing the use of mobile technology for technical English - Jano, Zanariah; Abdul Rahim, Razilah; Abdullah, Noridah; Khoo, Linda Mei Sui; Yeo, Mun Yee; Ahmad, Rabiah; Yusoff, Mariana; Jusoff, Kamaruzaman; Khamis, Noorli (American-Eurasian Network for Scientific Information, 2013)
Mobile technology in a new learning paradigm indicates the use of mobile and wireless technologies which scaffold the teaching and learning dimension in most tertiary institutions. The objective of this paper is to assess the level of students’ readiness in using a mobile technology for Technical English in one of the technical universities in Malaysia. A quantitative analysis was used through a survey method in which 200 survey questionnaires were sent out to randomly selected students in engineering faculties at the Universiti Teknikal Malaysia Melaka. The findings showed that the majority of students were ready to embark for a mobile-based learning as they had mobile phones equipped with a 3G service for class notes retrieval, multimedia messaging services, video call services for easy interaction among peers and with tutors. The results provide useful guidelines for curriculum designers and educators. Future work should integrate the perspectives of administrative units and educators to gain an overall assessment of the mobile technology readiness from various dimensions.